The Role of Olfactory Testing in Detecting Prodromal Phase Parkinson’s Disease: A Literature Review - Anastasia Ezragitha Soligaon Pasaribu; Melya Arianti Umbul (Universitas Pelita Harapan, 2026)
Introduction: Parkinson's disease (PD) is a progressive neurodegenerative disorder traditionally diagnosed based on classic motor symptoms. However, these motor manifestations appear only after a substantial loss of dopaminergic neurons in the substantia nigra. Detecting PD during its prodromal phase offers a crucial therapeutic window to potentially delay disease progression. Hyposmia is one of the earliest and most prevalent non-motor markers, appearing up to a decade before motor onset. Methods: A comprehensive literature search was conducted across electronic databases, including PubMed, Cochrane Library, and Google Scholar. The inclusion criteria were restricted to original research articles published within the last five years (2021–2026) in English or Indonesian. Data regarding olfactory testing accuracy and cultural adaptation were synthesized. Results: Standardized olfactory assessment tools, such as the University of Pennsylvania Smell Identification Test (UPSIT), Sniffin' Sticks, and the Brief Smell Identification Test (B-SIT), demonstrate high sensitivity (79%) and specificity (81%) in distinguishing PD from diagnostic mimics. Nevertheless, international screening tools frequently suffer from cross-cultural bias due to unfamiliarity with Western odorants. Emerging evidence indicates that adapting these instruments using locally familiar Asian and Indonesian olfactory stimuli (e.g., coffee, jasmine, aromatic ginger, and cajuput oil) significantly optimizes diagnostic accuracy. Conclusions: Brief olfactory assessments, particularly those tailored to regional and cultural settings, serve as highly effective, cost-efficient, and non-invasive screening instruments for prodromal PD detection within routine neurogeriatric clinical practice. Keywords: Parkinson's Disease, Olfactory Testing, Hyposmia, Prodromal Phase, Cross-Cultural Adaptation